Diagrammatic thinking – complexity handled between knowing and feeling - Berling Hyams, Inger (ARCC Conference Repository, 2014)
This paper explores a dual position of the diagram through Deleuzian theory and the theories of Frederik Stjernfelt and C.S. Peirce. I will try to demonstrate how diagrammatic drawing can take an intermediate position between knowing and feeling. For architects and designers, thought is continuously formed by drawings in an intuitive and sometimes unpredictable, but nonetheless intentional, manner. Such a thought process I have termed diagrammatic thinking. Through a deeper understanding of diagrammatic thought, tactics with which to approach architectural development can be articulated and thus in the end taught or exchanged. In this paper the tactic of abstraction is investigated and presented through the drawings of architecture students at Department 6 of the Danish Royal Academy, Architecture School. My findings are based on studies I have made of the drawing praxis at the department in 2011. Department 6 has an approach to architecture that does not only deal with environments that are to some extent already built upon, but also with elements that are not traditionally architectural, but connected to alternative organizations of urban flows, thoughts and memories. I present the notion of the fictive diagram as a model to understanding how this very aesthetic diagram praxis works.